2009
DOI: 10.1590/s1413-70542009000700006
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de características da carcaça e da qualidade da carne de queixada (Tayassu pecari [Link, 1795])

Abstract: RESUMONo presente trabalho, propôs-se avaliar os parâmetros de qualidade na carcaça e carne de queixadas adultas. Um total de quatro queixadas (três machos e uma fêmea), com peso vivo (PV) médio de 29,47 ± 3,45 kg, foi abatido, determinado o rendimento de carcaça quente (RCQ), e avaliada a área do olho do lombo (AOL), gordura de marmoreio (GM), espessura da gordura de cobertura (EGC), pH, perda de peso por cozimento (PPC), concentração de pigmentos heme totais (PHT) e composição centesimal no músculo Longissim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
8
0
2
Order By: Relevance
“…Regarding pH 45 we showed that the D 2 D 2 animals had a lower value than the others, Kauffman (Kauffman, 1991;Ramos et al, 2009) However, pH at 45 min is not a good indicator of the final quality of the meat according to Kauffman (1991) and Tomovic et al (2014), pH 45 <6 may be an indicator of pale, soft, and exudative meat and values above 6.3 are desirable for obtaining reddish, firm, non-exudative meat in the case of loin and leg muscles, which predominantly contain white fibers. However, the LC muscle consists predominantly of red fibers, which are an indicator of dark, firm, and dry (DFD) meat.…”
Section: Discussionmentioning
confidence: 77%
“…Regarding pH 45 we showed that the D 2 D 2 animals had a lower value than the others, Kauffman (Kauffman, 1991;Ramos et al, 2009) However, pH at 45 min is not a good indicator of the final quality of the meat according to Kauffman (1991) and Tomovic et al (2014), pH 45 <6 may be an indicator of pale, soft, and exudative meat and values above 6.3 are desirable for obtaining reddish, firm, non-exudative meat in the case of loin and leg muscles, which predominantly contain white fibers. However, the LC muscle consists predominantly of red fibers, which are an indicator of dark, firm, and dry (DFD) meat.…”
Section: Discussionmentioning
confidence: 77%
“…The meat color was evaluated using a Minolta Chroma Meter (model CR-400) on the surface of each sample, sliced with approximately 3 cm thickness and exposed to a refrigerated environment for 30 min, at approximately 4 °C (Ramos & Gomide, 2007), Three records for L*, a*, and b* were made, indicating lightness, redness, and yellowness of the meat samples, respectively (Muchenje et al, 2009). For the analysis of weight loss from cooking, the afore-mentioned steak was weighed and packed in aluminum foil and then cooked in a conventional oven under constant monitoring until the internal temperature reached 71 °C, measured with a thermometer attached to the steak (Ramos & Gomide, 2007). After cooking, samples were carefully dried, allowing the excess water to drain.…”
Section: Meat Qualitative Evaluationmentioning
confidence: 99%
“…Embora a produção de carne para consumo humano se encontre concentrada na exploração de bovinos, suínos e aves, há um grande interesse na disponibilização de novas fontes proteicas, especialmente oriundas da fauna silvestre, uma vez que, além de oferecer novos produtos ao mercado, resultam em vantagens econômicas e sociais, além de proteger tais espécies da extinção, pois cresce o número de animais criados em cativeiro, como é o caso do caititu (Ramos et al, 2009).…”
Section: Introductionunclassified